Performance of Structural Insulated Panels with Rigid Skins subjected to Windborne Debris Impacts-Experimental Investigations - Chen, Wensu; Hao, Hong (ELSEVIER, 2015)
Structural insulated panels (SIPs) are high-performance building materials used as building envelope for residential, industrial and light commercial construction. When the building envelope is impacted by windborne debris in Cyclonic area, the debris might perforate the panel resulting in dominant openings. Dominant openings in the building envelope might cause differential internal pressurization and result in the damage to the whole building structure. In the present study, the dynamic response of SIPs with Extended Polystyrene (i.e. EPS) foam core sandwiched by two rigid skins of Oriented Strand Board (i.e. OSB) or fiber cement board were experimentally investigated by using a pneumatic cannon system for windborne debris impact. The failure and damage modes under various projectile impact scenarios were observed and compared. The performances of the SIPs were examined quantitatively in terms of the projectile penetration length, and deformation and strain time histories of the back skin. The effects of various specimen configurations, impact locations, projectile impact velocities and boundary conditions on their performance were studied. The penetration resistance capacity of the SIPs to against windborne debris impact was analyzed.